Double-ended Synchronous Reluctance Motor Drive with Extended Constant Power Speed Ratio and Increased Power Factor. Issue 4 (25th February 2016) - Li, Silong; Sarlioglu, Bulent
Abstract: This article proposes a double-ended synchronous reluctance machine drive to increase the constant power speed ratio and the power factor of a synchronous reluctance machine. The proposed double-ended synchronous reluctance machine drive is formed by two inverters, one connected to an energy source and the other one connected to a floating capacitor bank for reactive power compensation. Two control strategies are presented: the unity power factor control can keep the power factor unity seen from the energy source side inverter under all operating conditions; the optimum inverter utilization control can increase torque output ability and the constant power speed ratio while increasing the power factor. Detailed modeling and simulation of the proposed double-ended synchronous reluctance machine drive are presented. Compared to the traditional single-inverter synchronous reluctance machine drive, the proposed drive is able to reduce the conversion ratio of the front-end DC/DC converter and the rating of each switching device. In addition, three-level voltage output of the proposed drive is also capable to reduce total harmonic distortion. In conclusion, the proposed drive is very attractive for applications for which a high power factor or reactive power regulation is required or when a high constant power speed ratio is desired.